Analisis Hukum Islam dan Hukum Nasional terhadap Penjatuhan Talak melalui Media Sosial - Muhammad Romi; Akmal Abdul Munir (Program Studi Magister Hukum Islam - UIN Bukittinggi, 2025)
This study aims to analyze Islamic law and national law in Indonesia regarding the imposition of divorce through social media. The focus of the study is directed at how Islamic law justifies divorce through social media as a valid written form of divorce, and how national law regulates formal divorce through the mechanism of the judicial institution. This study uses a qualitative method with a normative legal approach, namely examining the sources of classical and modern Islamic law, as well as the provisions of regulations in force in Indonesia, such as the Marriage Law, Compilation of Islamic Law, and other laws related to the law of divorce through social media. The results of this study indicate that Islamic law, divorce through social media is considered valid if it meets the requirements such as the existence of a clear or implied talaq statement accompanied by an intention, even though it is not said directly. On the other hand, in the Indonesian national legal system, divorce is only valid if it is decided by the Religious Court through a conference process. Thus, there is a difference in orientation between the two, namely Islamic law which emphasizes substantial and spiritual aspects, while national law emphasizes formality and procedure. Therefore, harmonization is needed between these two approaches so that the resolution of divorce cases can reflect the values of justice, welfare, and legal certainty in family and community life.